Transcriptional regulation of N6-methyladenosine orchestrates sex-dimorphic metabolic traits - Salisbury, David A; Casero, David; Zhang, Zhengyi; Wang, Dan; Kim, Jason; Wu, Xiaohui; Vergnes, Laurent; Mirza, Aashiq H; Leon-Mimila, Paola; Williams, Kevin J; Huertas-Vazquez, Adriana; Jaffrey, Samie R; et al. (Nature metabolism, 2021)
Males and females exhibit striking differences in the prevalence of metabolic traits including hepatic steatosis, a key driver of cardiometabolic morbidity and mortality. RNA methylation is a widespread regulatory mechanism of transcript turnover. Here, we show that presence of the RNA modification N6-methyladenosine (m6A) triages lipogenic transcripts for degradation and guards against hepatic triglyceride accumulation. In male but not female mice, this protective checkpoint stalls under lipid-rich conditions. Loss of m6A control in male livers increases hepatic triglyceride stores, leading to a more ‘feminized’ hepatic lipid composition. Crucially, liver-specific deletion of the m6A complex protein Mettl14 from male and female mice significantly diminishes sex-specific differences in steatosis. We further surmise that the m6A installing machinery is subject to transcriptional control by the sex-responsive BCL6–STAT5 axis in response to dietary conditions. These data show that m6A is essential for precise and synchronized control of lipogenic enzyme activity and provide insights into the molecular basis for the existence of sex-specific differences in hepatic lipid traits.Salisbury et al. show that hepatic lipogenic mRNA is regulated by m6A modifications in a sex-dependent and dietary-dependent manner, contributing to sex-specific differences in hepatic lipid metabolism.